Making friends with your Money? - A semiotic analysis of relationship communication strategies in the financial sector - Andersen, Poul Houman; Nielsen, Anne Ellerup (HERMES - Journal of Language and Communication in Business, 2001)
Hand in hand with the increased competition in the financial sector, relationship marketing has become an important part of general bank marketing. Relationship marketing is concerned with the initiation and management of long-term customer relationships through the development of loyalty programmes. However, so far little focus has been on the communication of the marketing brand, with respect to the bank’s communicative starting point for pursueing such strategies. This paper addresses the communicative platform of banks as pursuers of relationship marketing strategies. Using a semiotic mapping approach, we analyse the brand positions of two Danish banks in terms of brand values and marketing communication strategies. We conclude the paper by pointing to research and policy implications for academia and management.